Association between serum adropin levels and gestational diabetes mellitus; a case–control study. (2nd December 2015) - Beigi, Aboutaleb; Shirzad, Nooshin; Nikpour, Fatemeh; Nasli Esfahani, Ensieh; Emamgholipour, Solaleh; Bandarian, Fatemeh
Abstract: Gestational diabetes mellitus (GDM) is increasing worldwide. The aim of this study was to investigate the association between serum adropin concentration and GDM. In a case–control study, conducted in 2013, 40 pregnant women with GDM and 40 healthy pregnant women (controls) were evaluated. Fasting serum adropin and lipid concentration were measured during 24th–28th weeks of gestation for both groups. These factors were compared between the two groups using independent sample t -test. There was a significant difference in adropin levels between the two groups and mean adropin levels were lower in GDM group ( p : 0.016). There was no significant correlation between serum adropin levels and body mass index as well as fasting blood glucose (FBS) or serum lipid profile including high-density lipoprotein, low-density lipoprotein, cholesterol and triglyceride concentration ( p > 0.05). There was a significant association between adropin concentration and GDM even after using regression model for removing confounding factors (odds ratio = 0.681). Low serum adropin concentration is associated with GDM in Iranian pregnant women.